PENGARUH PROFESIONALISME GURU DAN SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU - Hapizoh, Hapizoh; Harapan, Edi; Destiniar, Destiniar (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This research aimed at determining the influence of teacher professionalism and headmaster supervision on teacher performance. This has implemented in SMP Negeri Sub Rayon 16 Sukarami District Palembang City. The quantitative is used for this research. Simple and multiple regression are used for this research methodology. The sample was 113 teachers of SMP Negeri Sub Rayon 16 Sukarami District Palembang City. Data collection techniques used a questionnaire. The result found that (1) there is significant influence of teacher professionalism on teacher performance; (2) there is significant influence of headmaster supervision on teacher performance; and (3) there is significant influence for both teacher professionalism and headmaster supervision on teacher performance.